2017
DOI: 10.17221/55/2016-pps
|View full text |Cite
|
Sign up to set email alerts
|

Potential of some bacteria for biological control of postharvest citrus green mould caused by Penicillium digitatum

Abstract: Mohammadi P., Tozlu E., Kotan R., Kotan Şenol M. (2017): Potential of some bacteria for biological control of postharvest citrus green mould caused by Penicillium digitatum. Plant Protect. Sci., 53: 134-143.Ten bacteria isolate (4 Bacillus subtilis, 2 Bacillus pumilus, 2 Bacillus cereus, 1 Bacillus megaterium, and 1 agrobacterium radiobacter) were tested in vitro for antagonistic properties against Penicillium digitatum, the causal agent of citrus green mould. The effect of these bacteria was also observed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 47 publications
(46 reference statements)
1
12
0
1
Order By: Relevance
“…Besides fungicides, other agricultural practices such as irradiation application (light emitting diode, gamma radiation, or UV radiation) [14,15,16,17], thermotherapy [18,19,20], biocontrol agents (BCA) [21,22,23], and salt solution [24,25] may be used to control postharvest diseases. In the past thirty years, there have been extensive research activities to explore and develop strategies based on microbial antagonists to biologically control postharvest pathogens [26,27,28,29,30].…”
Section: Alternative Control Methodsmentioning
confidence: 99%
“…Besides fungicides, other agricultural practices such as irradiation application (light emitting diode, gamma radiation, or UV radiation) [14,15,16,17], thermotherapy [18,19,20], biocontrol agents (BCA) [21,22,23], and salt solution [24,25] may be used to control postharvest diseases. In the past thirty years, there have been extensive research activities to explore and develop strategies based on microbial antagonists to biologically control postharvest pathogens [26,27,28,29,30].…”
Section: Alternative Control Methodsmentioning
confidence: 99%
“…This ecological feature of the rhizosphere provides carbon and energy sources to microorganisms, thereby facilitating a rapid rate of microbial growth and activity that can benefit the roots. While PGPR communities are able to colonize roots and stimulate plant growth 5 , it is possible to inoculate the rhizosphere artificially with more of the relevant PGPRs and increase their populations in the rhizosphere, thereby increasing the occurrence of benefits for plant roots.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, B. subtilis also exhibited antifungal activity against various foodborne pathogen such as P. digitatum. [13] reported that B. subtilis can inhibit the growth P. digitatum with 82.4 % inhibition zone when tested in in vivo dual culture tests by inhibiting the mycelial growth P. digitatum. However, despite showing promising antifungal activities against various fungal foodborne pathogens, the potency of P. flourescens and B. subtilis as antifungal for citrus postharvest pathogen have not yet reported.…”
Section: Introductionmentioning
confidence: 99%